Perubahan Gejala Leukorrhea Pada Remaja Putri Setelah Diberikan Intervensi Rebusan Daun Sirih Hijau Dan Merah - Okto Riristina Gultom; Harliyanti Muthma Innah Mashar; Angelia Merry Kartika (Indonesian Journal of Health Community, 2026)
Leukorrhea discharge is a reproductive health issue experienced by adolescent girls. This study aims to compare the effectiveness of these two types of betel leaf decoctions in reducing symptoms of vaginal discharge in adolescent girls. Study employed a quantitative method with a pre-experimental design using a two-group pretest-posttest approach. The study sample consisted of 68 adolescent girls experiencing pathological vaginal discharge at SMKN 3 Palangka Raya, selected using purposive sampling. The respondents were divided into two groups: the green betel leaf decoction group and the red betel leaf decoction group. The instruments used were a vaginal discharge questionnaire (12 items) and a standard operating procedure for therapy. Data analysis was conducted using univariate and bivariate methods, employing a paired t-test. The results showed a decrease in the mean discharge score in both groups. The green betel leaf group experienced a decrease from 18.09 to 17.26, whilst the red betel leaf group decreased from 19.03 to 15.76. Statistical analysis revealed a p-value of 0.0001 (<0.05), indicating a significant effect. The reduction was greater in the red betel leaf group (3.265) compared to the green betel leaf group (0.824). It was concluded that betel leaf decoction is effective as a non-pharmacological therapy.